Design, synthesis, antiviral bioactivity and three‐dimensional quantitative structure–activity relationship study of novel ferulic acid ester derivatives containing quinazoline moiety. Issue 10 (22nd May 2017) - Wu, Zengxue; Zhang, Jian; Chen, Jixiang; Pan, Jianke; Zhao, Lei; Liu, Dengyue; Zhang, Awei; Chen, Jin; Hu, Deyu; Song, Baoan
Abstract: BACKGROUND: Ferulic acid and quinazoline derivatives possess good antiviral activities. In order to develop novel compounds with high antiviral activities, a series of ferulic acid ester derivatives containing quinazoline were synthesized and evaluated for their antiviral activities. RESULTS: Bioassays indicated that some of the compounds exhibited good antiviral activities in vivo against tobacco mosaic virus (TMV) and cucumber mosaic virus (CMV). One of the compounds demonstrated significant curative and protective activities against TMV and CMV, with EC50 values of 162.14, 114.61 and 255.49, 138.81 mg L −1, respectively, better than those of ningnanmycin (324.51, 168.84 and 373.88, 272.70 mg L −1 ). The values of q 2 and r 2 for comparative molecular field analysis and comparative molecular similarity index analysis in the TMV (0.508, 0.663 and 0.992, 0.930) and CMV (0.530, 0.626 and 0.997, 0.981) models presented good predictive abilities. CONCLUSION: Some of the title compounds demonstrated good antiviral activities. Three‐dimensional quantitative structure–activity relationship models revealed that the antiviral activities depend on steric and electrostatic properties. These results could provide significant structural insights for the design of highly active ferulic acid derivatives. © 2017 Society of Chemical Industry